The Gratitude and Happiness of a Mother with a Child in Special Need - Ulfasari, Retty; Trimulyaningsih, Nita (Psikis : Jurnal Psikologi Islami, 2024)
This study aimed to investigate the relationship between gratitude and happiness in mothers of exceptional children. The research hypothesis in this study was a positive relationship between gratitude and happiness in mothers of exceptional children. The participants in this study were 65 mothers of exceptional children aged 18 - 60 years. This study used two scales, namely the happiness scale translated by Ramadhonna (2017), referring to The Subjective Happiness Scale (SHS) developed by Lyubomirsky and Lepper (1999). The gratitude scale, adapted from Surya (2016), refers to the aspect of the gratitude scale proposed by Al-Jauziyah (1998). The Pearson product-moment correlation coefficient was used to analyze the data in this study. The results of the data analysis showed that r = 0,520 with the significance p = 0,000 (p <0,05). The determination analysis (r2) showed that gratitude contributes 27% to the happiness of mothers of special needs children. Thus, it can be concluded that the hypothesis proposed in this study was accepted. The researcher also conducted additional analyses based on the demographic data, and then the discussions on the findings will be discussed further. Gratitude is highly recommended in interventions to increase happiness or well-being.